Determinants of Macroeconomic Indicators on The Level of Collection of Zakat, Infaq, Sadaqah (ZIS) Funds in BAZNAS 2005-2023 VECM Approach - Andriansyah Bastian; Erike Anggraeni; Gustika Nurmalia (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2024)
The researcher wants to examine the focus on inflation, GDP, and exchange rates, which are macroeconomic factors that influence the economy in the collection of ZIS funds in Baznas from 2005 to 2013, using the VECM approach. This type of research uses a quantitative approach. The data used is quantitative data obtained from secondary sources. This research approach uses an analytical method, namely the Vector Error Correction Model (VECM) with Eviews 12. The data used in this research is data from the Central Statistics Agency (BPS), the World Bank, the National Zakat Amil Agency (BAZNAS), and other literature discussing the relevant research material. This research shows no short-term relationship between the independent variables (Inflation and Exchange Rates) and the dependent variable (ZIS fund collection at Baznas) in 2005-2023. Meanwhile, there is a short-term relationship for the independent variable (Gross Domestic Product). However, there is a long-term relationship between the independent variables (Inflation and Exchange Rates) and the dependent variable (ZIS fund collection at BAZNAS) in 2005-2023. The independent variable (Gross Domestic Product) does not have a long-term relationship, and simultaneously, the inflation, exchange rate, and PDB variables significantly affect the collection of ZIS funds at BAZNAS.